Pengaruh Citra Merek dan Kualitas Layanan Terhadap Loyalitas Pelanggan Pada Kedai Kopi Kenangan. - Namira Saula rizkianti; Niken Herawati (Sekolah Tinggi Ilmu Manajemen Indonesia YAPMI, 2026)
This study aims to determine the Influence of Brand Image and Service Quality on Customer Loyalty at the Kenangan Coffee Shop in Sukahati Cibinong. The sample used in this study was 96 respondents, taken using purposive sampling and to determine the size or number of samples used the lemeshow formula. Data collection techniques through observation, interviews and documentation studies in the form of primary data, namely distributing questionnaires using Google Form. Data analysis used data quality tests, classical assumption tests, regression coefficient tests and hypothesis tests. The results of this study are that Brand Image partially has a positive and significant effect on Customer Loyalty with a t-count value of 6.520 and a significance of 0.000. Service Quality partially has a positive and significant effect on Customer Loyalty with a t-count value of 2.874 and a significance of 0.000. The results of the f test obtained a significance value of 0.000 less than 0.05 and an f-count value of 103.883 greater than the f-table of 3.09, which means that together brand image and service quality have a significant positive effect on customer loyalty.